Hereditary blood diseases in Jeddah (Sickle Cell Anemia – Thalassemia) - Al-Lail, Amna Sami Jamal; Al-Obaidi, Nadia Rafed (Journal of medical and pharmaceutical sciences, 2024)
The study examined the economic and social characteristics of patients with Sickle Cell Anemia and Mediterranean Anemia in the city of Jeddah. They are among the hereditary blood diseases spread throughout the Kingdom of Saudi Arabia. The study aims to identify the economic and social characteristics of patients and reveals the relationship between parents undergoing pre-marital examination and transmission of the disease. To achieve this goal, the study relied on the field study approach to collect data through the use of a questionnaire and distributing it to patients. The study showed that 90% of people with the disease had parents that didn’t take a pre-marital test, which indicates the presence of a significant relationship between parents undergoing pre-marital examination and transmission of the disease. The study also showed that 75.6% of patients fathers have stopped school education after primary school, and 33.3% of patients mothers are illiterate or cannot read or write. The researcher recommends the necessity of issuing laws and legislation that regulate or oblige both parties to the marriage to take the results of the examination into account and not to complete the marriage if it is an unsafe marriage, that is, there is a high possibility of transmitting the disease to children.